Adaptation Of Non-Sundanese Reporters In Collecting News In Bandung City - Maila Siti Nurmala; Darajat Wibawa; Khoiruddin Muchtar (INJECT (Interdisciplinary Journal of Communication), 2020)
The adaptation of non-Sundanese reporters is the object of this study; the aim is to find out the views of non-Sundanese journalists on Sundanese society in the city of Bandung, the self-concept owned by non-Sundanese journalists and how the adaptation of non-Sundanese journalists in gathering news. The methodology used is phenomenology with symbolic interaction theory. This study uses a qualitative approach: observation techniques, in-depth interviews do the process of data collection. The results showed that Non-Sundanese Journalists in Bandung City, most of the opinion. Sundanese people have a positive nature and easy to accept other people from outside the region who have cultural differences. For non-Sundanese journalists, when carrying out their profession as a journalist, they should have advantages compared to indigenous journalists so that they can survive in carrying out their duties in gathering news. Having education that is directed and professional in their fields, is capital in carrying out their profession so that they will become journalists who are expected and needed by others, wherever they are. Non-Sundanese journalists are expected to be able to adapt or adjust to the perceived differences in gathering news, especially from cultural and linguistic differences, so that enormous courage and patience are needed.